Development of a Break-Even Analysis (BEA) model for setting the selling price of marine product MSMEs - Vina Olivia Pebrianty; Si Made Ngurah Purnaman; Syaiah Syaiah; Hasnidar Hasnidar; Aisyah Muthiah Salsabila (Privietlab, 2026)
This study aims to develop an applicative Break-Even Analysis (BEA) model to support pricing decisions for seafood processing MSMEs in Kendari City. Most MSMEs in this sector still set selling prices intuitively due to a limited understanding of cost accounting and incomplete financial records. This study employed a descriptive quantitative approach with a field study design, using questionnaires, interviews, observations, and documentation to collect data from MSMEs that met the research criteria. The BEA model was developed based on fixed costs, variable costs, production volume, and selling price. The results indicate that the BEA model is easy to apply, suitable for MSMEs with simple bookkeeping practices, and capable of generating accurate break-even points and minimum selling price calculations. After applying the model, MSME owners demonstrated an improved understanding of cost structures and were able to determine selling prices and profit margins more rationally. These findings confirm that BEA enhances cost awareness and supports more efficient decision-making. Overall, this study provides a practical managerial tool that can be utilized by MSMEs, local government agencies, and academic institutions to strengthen financial literacy and pricing strategies in the seafood-processing sector.